Are we moving to an early intervention approach in forensic adolescent services?. Issue 4 (4th July 2022) - Smith, Alex; Law, Heather; Millington, James; Parker, Sophie; White, Oliver; Imran, Shermin
ABSTRACT: Aims and Method A retrospective service evaluation of the first 500 referrals to a new community forensic service (FCAMHS) describing profiles of young people accessing the service. The evaluation aims to understand the impact of changes in health service care models and diversion from youth justice services over the last two decades in England. Accessibility to enhance opportunity for prevention of high-risk behaviours for all ages up to 18 is evaluated. Results The majority of referrals were living with their families, had no social care status, attended mainstream school and had an average age of 14 (range 7–18). Most referrals were for aggression, followed by harmful sexual behaviour and fire setting. Half the referrals had no formal mental health diagnosis or criminal status. Neurodevelopmental disorders were present in a quarter of referrals. Despite lower numbers of female referrals, the reasons for referral were similar to males. Clinical Implications The service evaluation highlights the changing face of forensic services and the move towards early intervention by pioneering an accessible and flexible model of care.